2021
DOI: 10.1186/s13020-021-00436-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion variation of ginsenoside CK mediated by human gut microbiota from healthy volunteers and colorectal cancer patients

Abstract: Background Ginsenoside CK (GCK) serves as the potential anti-colorectal cancer (CRC) protopanaxadiol (PPD)-type saponin, which could be mainly bio-converted to yield PPD by gut microbiota. Meanwhile, the anti-CRC effects of GCK could be altered by gut microbiota due to their different diversity in CRC patients. We aimed to investigate the bioconversion variation of GCK mediated by gut microbiota from CRC patients by comparing with healthy subjects. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Ginseng, as a treasure of human pharmaceutical culture, contains a variety of active components, among which ginsenoside is the main bioactive compound in ginseng and has broad implications in human disease [ 16 ]. Ginsenoside CK is a natural diol-type ginsenoside with medicinal activity in vivo [ 17 ]. Studies found that Ginsenoside CK has inhibiting effects on various tumor cells, containing lung cancer, colon cancer, and liver cancer, as well as bone tumor [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ginseng, as a treasure of human pharmaceutical culture, contains a variety of active components, among which ginsenoside is the main bioactive compound in ginseng and has broad implications in human disease [ 16 ]. Ginsenoside CK is a natural diol-type ginsenoside with medicinal activity in vivo [ 17 ]. Studies found that Ginsenoside CK has inhibiting effects on various tumor cells, containing lung cancer, colon cancer, and liver cancer, as well as bone tumor [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that GC-K can play a bene cial role in colitis by inhibiting IRAK-1 and NF-kB activation [12]. However, the absolute oral bioavailability of GC-K is only about 35% [13], which implied it could interplay with gut microbiota after oral administration [14]. Recently, natural products have been discovered to interplay with gut microbiota in vivo [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the absolute oral bioavailability of GC-K is only about 35% [13]. GC-K is catalyzed by β-glycosidase only secreted from gut microbiota to generate its metabolite protopanaxadiol in vivo, which implies that GC-K interplays with gut microbiota after oral administration [14]. Furthermore, our previous study found that GC-K could suppress the tumor growth of AOM/DSS-induced colitis-associated CRC through the modulation of gut microbiota, partially by up-regulation of A. muciniphila [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng, as a treasure of human pharmaceutical culture, contains a variety of active components, among which ginsenoside is the main bioactive compound in ginseng and has broad implications in human disease [16]. Ginsenoside CK is a natural diol-type ginsenoside with medicinal activity in vivo [17]. Studies found that Ginsenoside CK has inhibiting effects on various tumor cells, containing lung cancer, colon cancer, and liver cancer, as well as bone tumor [18][19][20].…”
Section: Discussionmentioning
confidence: 99%